Development of digital audio storybook media to improve early reading skills in first-grade elementary school students - Arifa, Noorul; Herwin, Herwin (Jurnal Penelitian Ilmu Pendidikan, 2024)
This study aimed to develop and evaluate the feasibility, practicality, and effectiveness of a digital audio storybook as a learning medium for improving early reading skills in first-grade students. Conducted within the Trimulyo Cluster, Kapanewon Sleman, this Research and Development (R&D) study employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through interviews, observations, questionnaires, and reading assessments. Validation from experts indicated the media’s feasibility, scoring an average of 3.8 from a material expert and 4.0 from a media expert. Practicality was confirmed through high average scores from teacher (94.44%) and student (ranging from 90.83% to 93.89%) feedback. Effectiveness was measured via a quasi-experimental design, showing an N-Gain score of 80.75% and a statistically significant improvement (p < 0.05). In conclusion, the developed digital audio storybook is proven to be feasible, practical, and effective for early reading instruction in primary education. It presents an innovative and impactful learning tool that can significantly support literacy development in young learners.